A NEW CONCEPT OF MODELING NEEDS OF THE POPULATION IN THE LABOR MOVEMENT BY PUBLIC TRANSPORT - Ghorbachov, P. F. (Science and Transport Progress, 2009)
In the paper, with the purpose of accounting a casual character of distribution of capacities of transport areas on labor movements in a matrix of correspondences, the interval concept of modeling the population needs in movements has been suggested when for transport calculations one uses not one variant of a matrix but borders of an interval of its possible values at the set area capacities.